The Impact of Energy Price Changes in Moldova - Baclajanschi, Iaroslav (World Bank, Washington, DC, 2012)
In January 2006 the price of natural gas supplied to Moldova increased from $80 to $110 per thousand cubic meters (mcm). Prices may increase further in the near future, putting additional pressure on the economy and leading to adverse effects on the poorest households. This study examines the potential impact of higher energy prices on the economy of Moldova by simulating the likely macroeconomic consequences of recent and future price increases. Moreover, it estimates the direct impact on individual households using data drawn from the 2004 Household Budget Survey. It assesses the distributional implications of the price shock, noting how the social impact may vary depending on the intensity of energy use, geographic location, and the relative share of energy in household expenditure. The results suggest that energy price changes could dampen economic growth while putting additional strains on the current account deficit. The impact on the poorest households could be significant and protecting them may require resources in the amount of 0.7 to 1.7 percent of GDP. This study identifies possible policy responses to dampen the shock of the energy price increase and to promote the longer-term objective of reducing energy vulnerability.